Una «geologia di silenzi». Tratti della Gorizia letteraria e geografia poetica dell’afasia (ENTHYMEMA, 2020)
The essay aims to show connections between the works of Carlo Michelstaedter and those of Gian Giacomo Menon, poets and philosophers from Gorizia, and to discuss the spatial implications of their intertextual relationship. By referring to Alberto Comparini’s Geocritica e poesia dell’esistenza (2018) and employing the category of aphasia to analyse their works, the study will outline some fundamental traits of the poetic geography of Gorizia itself. Michelstaedter and Menon’s pre- and post-existentialism will be presented as linked to such an intertextuality and to the city where they were born. Besides, the presence of the geography of north-eastern Italy in Menon’s geologia di silenzi (2018) will be pointed out.
Keywords: Michelstaedter; Menon; Aphasia; Existentialism; Geocriticism; Poetic geography; Gorizia